2021
DOI: 10.3389/fneur.2021.749798
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Continuous Theta Burst TMS in the Neurorehabilitation of Subacute Stroke Patients: A Placebo-Controlled Study

Abstract: Objectives: Transcranial magnetic stimulation, in particular continuous theta burst (cTBS), has been proposed for stroke rehabilitation, based on the concept that inhibition of the healthy hemisphere helps promote the recovery of the lesioned one. We aimed to study its effects on cortical excitability, oscillatory patterns, and motor function, the main aim being to identify potentially beneficial neurophysiological effects.Materials and Methods: We applied randomized real or placebo stimulation over the unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Four out of thirteen articles investigated upper limb functions through transcranial stimulation (Nicolo et al, 2018;Ding et al, 2021;Dionísio et al, 2021;Kuzu et al, 2021). Dionísio et al (2021) compared cTBS vs. placebo stimulation, finding that contralateral inhibitory stimulation led to a significant excitatory impact on the cortical oscillatory beta band patterns of the contralateral affected hemisphere.…”
Section: Intervention Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four out of thirteen articles investigated upper limb functions through transcranial stimulation (Nicolo et al, 2018;Ding et al, 2021;Dionísio et al, 2021;Kuzu et al, 2021). Dionísio et al (2021) compared cTBS vs. placebo stimulation, finding that contralateral inhibitory stimulation led to a significant excitatory impact on the cortical oscillatory beta band patterns of the contralateral affected hemisphere.…”
Section: Intervention Protocolsmentioning
confidence: 99%
“…Four out of thirteen articles investigated upper limb functions through transcranial stimulation (Nicolo et al, 2018;Ding et al, 2021;Dionísio et al, 2021;Kuzu et al, 2021). Dionísio et al (2021) compared cTBS vs. placebo stimulation, finding that contralateral inhibitory stimulation led to a significant excitatory impact on the cortical oscillatory beta band patterns of the contralateral affected hemisphere. In Ding's (2021) study, the authors found that iTBS modulates brain network functioning in stroke survivors, normalizing brain connections, re-gaining the natural oscillation frequency, and promoting motor function recovery.…”
Section: Intervention Protocolsmentioning
confidence: 99%
“…It is pleasing to observe the notable success of our intervention in augmenting bladder function, kidney function, and overall quality of life, as well as mitigating symptoms of anxiety and depression among the patients. According to Dionísio et al, when cTBS is applied over the contralesional primary motor cortex of subacute post-stroke patients (within 7 ± 3 days), it results in an increase in cortical excitability and motor function in the ipsilesional hemisphere [17]. As a result, the patient's muscle strength and balance showed improvement, although it is important to note that this outcome can be attributed to a combination of conventional physical therapy and cTBS.…”
Section: Figure 3: Neural Control Process Of Urinationmentioning
confidence: 99%
“…TMS has been reported to have neuroprotective effects in a variety of neurological disorders, such as Alzheimer’s disease ( Mimura et al, 2021 ), Parkinson’s ( Chen and Chen, 2019 ), multiple sclerosis ( Aloizou et al, 2021 ), depression ( Toth et al, 2022 ), vascular dementia ( Nardone et al, 2011 ), and stroke ( Tosun et al, 2017 ). Some studies have shown that TMS combined with a variety of rehabilitation treatments can significantly reduce neurological dysfunction, improve the ability to perform activities of daily living, and improve the quality of life of stroke patients ( Dionísio et al, 2021 ; Hoonhorst et al, 2021 ; Zong et al, 2022 ). This suggests that TMS is a feasible adjunctive treatment for stroke.…”
Section: Introductionmentioning
confidence: 99%